2018
DOI: 10.1136/ebmental-2018-300040
|View full text |Cite
|
Sign up to set email alerts
|

Twenty years of progress in paediatric psychopharmacology: accomplishments and unmet needs

Abstract: The systematic assessment of the efficacy and safety of psychiatric medications in children and adolescents started about 20 years ago. Since then, a considerable number of randomised clinical trials have been conducted, including also a series of publicly funded comparative effectiveness studies to evaluate the therapeutic benefit of medications relative to psychosocial interventions, alone or combined with medications. On the whole, these studies have been informative of the paediatric pharmacokinetics, effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 54 publications
0
10
0
4
Order By: Relevance
“…We found that venlafaxine had a significantly increased risk for suicidality (suicidal behaviour or ideation) for young people, which is in line with previous reviews. 10,11 Two US medical claims databases that contain data on 221 028 young people with depression for the period 2004-09 showed that, after accounting for the time varying effect of confounders, the apparent association between antidepressant use and suicide attempts and selfinflicted injury was diminished and not statistically significant. 33 Antidepressant use by adolescents had previously been increasing but declined abruptly after the warnings were introduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that venlafaxine had a significantly increased risk for suicidality (suicidal behaviour or ideation) for young people, which is in line with previous reviews. 10,11 Two US medical claims databases that contain data on 221 028 young people with depression for the period 2004-09 showed that, after accounting for the time varying effect of confounders, the apparent association between antidepressant use and suicide attempts and selfinflicted injury was diminished and not statistically significant. 33 Antidepressant use by adolescents had previously been increasing but declined abruptly after the warnings were introduced.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 The mean effects (standardised mean differ ence [SMD] -0•29) after treatment were more modest than those found for treatment of other youth problems, including anxiety (SMD -0•61), attention deficit hyper activity disorder (SMD -0•34), and conductrelated problems and disorders (SMD -0•46). 9 Previous metaanalyses 10,11 have shown that anti depres sants, except for fluoxetine, do not offer a clear advantage over pill placebo for many individuals, and some antidepressants might increase risk of suicidality. The mean effects of antidepressants for major depressive disorder compared with pill placebo (Hedges g 0•21 for selective serotonin reuptake inhibitor [SSRI] and 0•16 for serotonin-norepinephrine reuptake inhibitor [SNRI]) have been more modest than those found for treatment of other youth problems, including anxiety disorder (Hedges g 0•71 for SSRI and 0•41 for SNRI) and obsessivecompulsive disorder (Hedges g 0•39 for SSRI).…”
Section: Introductionmentioning
confidence: 99%
“…The risk of bias and the quality of evidence of the individual studies varied and was assessed with different approaches across the included systematic reviews/meta-analyses. Even though randomised controlled trials are at the top of the hierarchy of evidence and have been used over the past 20 years to assess the effect of pharmacological interventions in children and adolescents ( 35 ), they may have limited generalizability and may be prone to sponsorship bias ( 36 ). Second, the overall quality of the systematic reviews retained in our meta-review, rated via the AMSTAR-2 tool ( 8 ), was variable, ranging from high for the network meta-analysis on ADHD ( 10 ) to critically low for the evidence synthesis on anxiety ( 11 ) and enuresis ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a comprehensive overview of the advances and challenges of child and adolescent psychopharmacology, Vitiello and Davico2 highlight how the past two decades of research in this area have been progressively shaped by the evidence-based approaches. Nevertheless, there is still a long way to move from symptom improvement to disease-modifying interventions, especially with relevance to treatment effects in usual practice conditions.…”
mentioning
confidence: 99%
“…Nevertheless, there is still a long way to move from symptom improvement to disease-modifying interventions, especially with relevance to treatment effects in usual practice conditions. The review by Vitiello and Davico2 is also nicely completed by the paper authored by Baker and Carlson,3 who, after an extensive literature search, were able to identify only 10 studies using Pro Re Nata (PRNs) to manage agitated outbursts in children and adolescents in acute care settings and most were chart reviews. In fact, the only placebo-controlled trial of PRN medications was done by Vitiello and colleagues in 19904 which showed that placebo worked as well as active drug!…”
mentioning
confidence: 99%